Report to the secretary of state for the home department by two of H.M. inspectors of factories. Appointed to enquire into the conditions of work in the fish-curing trade of the United Kingdom. Presented to both Houses of Parliament by command of Her Majesty (Darling, 1898)
Factory and workshop (fish-curing trade).